Dysregulation of secondary bile acid metabolism precedes islet autoimmunity and type 1 diabetes - Lamichhane Santosh; Sen Partho; Dickens Alex M.; Alves Marina Amaral; Härkönen Taina; Honkanen Jarno; Vatanen Tommi; Xavier Ramnik J.; Hyötyläinen Tuulia; Knip Mikael; Oresic Matej (ELSEVIER, 2022)
The gut microbiota is crucial in the regulation of bile acid (BA) metabolism. However, not much is known about the regulation of BAs during progression to type 1 diabetes (T1D). Here, we analyzed serum and stool BAs in longitudinal samples collected at 3, 6, 12, 18, 24, and 36 months of age from children who developed a single islet autoantibody (AAb) (P1Ab; n = 23) or multiple islet AAbs (P2Ab; n = 13) and controls (CTRs; n = 38) who remained AAb negative. We also analyzed the stool microbiome in a subgroup of these children. Factor analysis showed that age had the strongest impact on both BA and microbiome profiles. We found that at an early age, systemic BAs and microbial secondary BA pathways were altered in the P2Ab group compared with the P1Ab and CTR groups. Our findings thus suggest that dysregulated BA metabolism in early life may contribute to the risk and pathogenesis of T1D.